Antisickling Drugs Targeting βCys93 Reduce Iron Oxidation and Oxidative Changes in Sickle Cell Hemoglobin - Kassa, Tigist; Wood, Francine; Strader, Michael Brad; Alayash, Abdu I. (Frontiers in Physiology, 2019)
Sickle cell disease is a genetic blood disorder caused by a single point mutation in the β-globin gene where glutamic acid is replaced by valine at the sixth position of the β-chain of hemoglobin (Hb). At low oxygen tension, the polymerization of deoxyHbS into fibers occurs in red blood cells (RBCs) leading to an impaired blood vessel transit. Sickle cell hemoglobin (HbS), when oxidized with hydrogen peroxide (H2O2), stays longer in a highly oxidizing ferryl (Fe+4) form causing irreversible oxidation of βCys93 to a destabilizing cysteic acid. We have previously reported that an antisickling drug can be designed to bind specifically to βCys93 and effectively protect against its irreversible oxidation by H2O2 (Kassa et al., 2017). Here we report oxygen dissociation, oxidation and polymerization kinetic reactions for four antisickling drugs (under different preclinical/clinical developmental stages) that either site specifically target βCys93 or other sites on the HbS molecule. Molecules that specifically bind to or modify βCys93, such as 4,4'-Di(1,2,3-triazolyl) disulfide (TD-3), and hydroxyurea (HU) were contrasted with molecules that target other sites on Hb including 5-hydroxymethyl-2-furfural (5-HMF), and L-glutamine. All reagents induced a left shift in the oxygen dissociation curve (ODC) except L-glutamine. In the presence of H2O2 (2.5:1, H2O2:heme) both TD-3 and HU reduced the ferryl heme by 22% and 37% respectively which corresponded to a 3 to 2-fold reduction in the levels of βCys93 oxidation as verified by mass spectrometry. Increases in the delay times prior to polymerization of HbS under hypoxia were in the following order: TD-3>HU>5-HMF=L-glutamine. Designing antisickling agents that can specifically target βCys93 may provide a dual antioxidant and antisickling therapeutic benefits in treating this disease.